In vitro and in vivo gene expression studies of cartilage-like tissue engineered construct using a combination of transiently transfected human osteoarthritic chondrocytes and tissue engineering technique - Sha'ban, Munirah; Mohamad Sukri, Norhamiza; Zulkifly, Ahmad Hafiz (Frontiers Media, 2016)
Purpose: To evaluate the formation of cartilage-like tissue engineered constructs (TECs) using human osteoarthritic chondrocytes overexpressed with SOX9 gene seeded on poly(lactic-co-glycolic acid) (PLGA) with and without fibrin scaffolds through cartilaginous genes expression analysis.